Firm’s Networking Competencies: Learning Orientation, Degree Of Internationalisation And The Role Of Strategic Motivation - Boumediene, Kebaili (2010)
In the current environmental context, organisations are facing tremendous pressure caused by several factors like globalisation and technological development. Consequently, firms are looking for different business models to deal with these issues. Inter-firm collaboration has been revealed as a prime source for developing distinctive competencies. Within this context, the research proposes networking competencies for firms to sustain their international growth. More specifically, this study examines the impact of learning orientation on firm networking competencies, and firm’s degree of internationalization as an outcome the firm networking competencies. The research, also, investigate the moderating role of strategic motivations using the social exchange theory and contingency theory. A model depicting relationships between these variables was developed based on the literature review. Adopting survey method, the model was tested using data gathered from 137 firms operating in the Malaysian manufacturing industry. The results reveal that two antecedents are positively related to the firm networking competencies. The results also indicate that firm networking competencies are significant predictors of the firm degree of internationalisation. Based on the findings theoretical contributions, implications were discussed for managers and policymakers. Finally, the study concludes with a number of limitations and directions for future research.